Answers

2014-10-13T23:15:25+08:00
Using elimination method:
4x - 5y = -8  ----equation 1
-x + 3y = 2 -----equation 2
multiply equation 2 with 4
(-x + 3y = 2) x 4
-4x + 12y = 8 ----equation 2'
add equations 2' and 1
   -4x + 12y = 8
+  4x  -  5y = -8
             7y = 0
              y =0
multiply equation 1 with 3 and equation 2 with 5
(4x - 5y = -8) x 3
(-x + 3y = 2) x 5
12x -15y = -24
-5x +15y= 10
add both equations
7x = -14
x = -2

Using substitution method:
4x - 5y = -8  ----equation 1
-x + 3y = 2 -----equation 2
rearranging equation 2 you'll have:
-x + 3y = 2
x = 3y -2 ----equation 3
substitute equation 3 to equation 1
4x - 5y = -8
4(3y - 2) - 5y = -8
12y - 8 - 5y = -8
7y = -8 + 8
7y = 0
 y = 0
substituting the value of y to equation 3 you'll have
x = 3y - 2
x = 3(0) - 2
x = -2
0